2006
DOI: 10.1111/j.1468-2478.2006.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

ABC's, 123's, and the Golden Rule: The Pacifying Effect of Education on Civil War, 1980?1999

Abstract: This study examines two ways by which education might affect the probability of civil war onset. First, educational investment provides a strong signal to the people that the government is attempting to improve their lives, which is apt to lower grievances, even in desperate times. Second, education can generate economic, political, and social stability by giving people tools with which they can resolve disputes peacefully, making them less likely to incur the risks involved in joining a rebellion. This theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
159
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 62 publications
19
159
3
Order By: Relevance
“…Of the thirty studies reviewed, Ostby and Urdal (2010) [2] find that only seven of them (Barakat and Urdal (2009) [3], Berrebi (2007) [6], Fair (2008) [7], Krueger and Malečkova (2003) [4], Oyefusi (2008) [8], Shayo (2007) [9], and Thyne (2006) [5]) have the word "education" as a part of the title and among these the vast majority are micro-level studies. Interestingly, most of the macro-and meso-level studies have focused on the conflict potential of various levels of education, as Ostby and Urdal (2010) [2] suggest.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the thirty studies reviewed, Ostby and Urdal (2010) [2] find that only seven of them (Barakat and Urdal (2009) [3], Berrebi (2007) [6], Fair (2008) [7], Krueger and Malečkova (2003) [4], Oyefusi (2008) [8], Shayo (2007) [9], and Thyne (2006) [5]) have the word "education" as a part of the title and among these the vast majority are micro-level studies. Interestingly, most of the macro-and meso-level studies have focused on the conflict potential of various levels of education, as Ostby and Urdal (2010) [2] suggest.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while there is broad empirical evidence in support of the premise that secondary enrolment-the dimension most researched in the education-conflict empirical literaturepacifies conflict, the few studies which have examined the tertiary dimension of education (notably, Thyne (2006) [5], Urdal (2008) [10], Bussmann (2007) [11] and Besançon (2005) [12]) do not suggest a clear relationship between tertiary education and conflict risk 2 . Ostby and Urdal (2010) [2] have recently concluded that "it is still unclear whether (and if) tertiary education is related to conflict risk".…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations